3-Azidoazetidines as the first scaffolds for β-amino azetidine carboxylic acid peptidomimetics: azetidine iminosugars containing an acetamido group do not inhibit β-N-acetylhexosaminidases. Issue 17 (1st October 2016) - Liu, Zilei; Jenkinson, Sarah F.; Kato, Atsushi; Nakagawa, Shinpei; Wormald, Mark R.; Yu, Chu-Yi; Fleet, George W.J.
Graphical abstract: Abstract: Stable amides and oligopeptides derived from methyl trans, trans -3-azido-4-hydroxymethyl-l -azetidine carboxylate, prepared in 19% yield from diacetone allose, is the first example of a β-amino-azetidine carboxylic acid incorporated into peptidomimetics and provides a scaffold for investigating secondary structure induced by a novel β-amino acid. A number of azetidine iminosugars containing a NHAc substituent were prepared but none of them were β- N -acetylhexosaminidase inhibitors. Abstract : 3-Azido-3-deoxy-1, 2:5, 6-di- O -isopropylidene-α-d -glucofuranose: C12 H19 N3 O5 [ α ]D 20  = −47.5 ( c 1.2, CHCl3 ) Source of chirality:d -glucose Abstract : 3-Azido-3-deoxy-1, 2- O -isopropylidene-α-d -glucofuranose: C9 H15 N3 O5 mp: 80–82 °C [ α ]D 20  = −32.7 ( c 0.47 in CHCl3 ) Source of chirality:d -glucose Abstract : 3-Azido-3-deoxy-1, 2- O -isopropylidene-α-d -xylofuranose: C8 H13 N3 O4 mp 68–70 °C [ α ]D 20  = −57.8 ( c 0.38 in CHCl3 ) Source of chirality:d -glucose Abstract : 3-Azido-3-deoxy-d -xylopyranose: C5 H9 N3 O4 mp 72–74 °C Source of chirality:d -glucose Abstract : 3-Azido-3-deoxy-1, 2, 4-tri- O -acetyl-d -xylopyranose: C11 H15 N3 O7 mp 46–48 °C Source of chirality:d -glucose Abstract : Methyl 3-azido-3-deoxy-2, 4-di- O -acetyl-β-d -xylopyranoside: C10 H15 N3 O6 [ α ]D 20  = −65.0 ( c, 0.72 in CHCl3 ) Source of chirality:d -glucose Abstract : Methyl 3-azido-3-deoxy-β-d -xylopyranoside: C6 H11 N3 O4 mp 48–50 °C [ α ]D 20  = −31.1 ( c, 0.55 in CHCl3 ) Source of chirality:d -glucose Abstract : Methyl 3-azido- N -benzyl-2, 3, 4-trideoxy-2, 4-imino-β-l -riboside: C13 H16 N4 O2 [ α ]D 20  = −47.4 ( c 0.72 in CHCl3 ) Source of chirality:d -glucose Abstract : Methyl 3-azido- N -benzyl-2, 4-imino-2, 3, 4-trideoxy-l -ribonate: C13 H16 N4 O3 [ α ]D 20  = −39.6 ( c, 0.50 in CHCl3 ) Source of chirality:d -glucose Abstract : Methyl 3-azido- N -benzyl-2, 4-imino-2, 3, 4-trideoxy-l -ribonamide: C13 H17 N5 O2 [ α ]D 20  = −10.5 ( c, 0.50 in CHCl3 ) Source of chirality:d -glucose Abstract : Methyl 3-acetamido- N -benzyl-2, 4-imino-2, 3, 4-trideoxy-l -ribonamide: C15 H21 N3 O3 [ α ]D 20  = +56.4 ( c, 0.90 in CHCl3 ) Source of chirality:d -glucose Abstract : Methyl 3-acetamido-2, 4-imino-2, 3, 4-trideoxy-l -ribonamide: C8 H15 N3 O3 [ α ]D 20  = +112.5 ( c 0.30 in CHCl3 ) Source of chirality:d -glucose Abstract : 3-Azido- N -benzyl-1, 5-di- O -acetyl-2, 4-imino-2, 3, 4-trideoxy- meso -ribitol: C16 H20 N4 O4 [ α ]D 20  = 0 ( c 0.81 in CHCl3 ) Source of chirality:d -glucose Abstract : 3-Acetamido- N -benzyl-1, 5-di- O -acetyl-2, 4-imino-2, 3, 4-trideoxy- meso -ribitol: C18 H24 N2 O5 [ α ]D 20  = 0 ( c 1.0 in CHCl3 ) Source of chirality:d -glucose Abstract : 3-Acetamido- N -benzyl-2, 4-imino-2, 3, 4-trideoxy- meso -ribitol: C14 H20 N2 O3 [ α ]D 20  = 0 ( c 1.2 in MeOH) Source of chirality:d -glucose Abstract : 3-Acetamido-2, 4-imino-2, 3, 4-trideoxy- meso -ribitol: C7 H14 N2 O3 [ α ]D 20  = 0 ( c 1.0 in H2 O) Source of chirality:d -glucose Abstract : Methyl 3-azido- N -benzyl-5- O - (tert -butyldimethylsilyl)-2, 4-imino-2, 3, 4-trideoxy-l -ribonate: C19 H30 N4 O3 Si [ α ]D 20  = +55 ( c 0.36 in CHCl3 ) Source of chirality:d -glucose